A dietary pattern of frequent plant-based foods intake reduced the associated risks for atopic dermatitis exacerbation: Insights from the Singapore/Malaysia cross-sectional genetics epidemiology cohort - Jun Jie Lim; Kavita Reginald; Yee-How Say; Mei Hui Liu; Fook Tim Chew (BMC, 2023)
Abstract Background The prevalence of atopic dermatitis (AD) has been increasing in recent years, especially in Asia. There is growing evidence to suggest the importance of dietary patterns in the development and management of AD. Here, we seek to understand how certain dietary patterns in a Singapore/Malaysia population are associated with various risks of AD development and exacerbation. Methods A standardized questionnaire following the International Study of Asthma and Allergies in Childhood (ISAAC) guidelines was investigator-administered to a clinically and epidemiology well-defined allergic cohort of 13,561 young Chinese adults aged 19-22. Information on their sociodemographic, lifestyle, dietary habits, and personal and family medical atopic histories were obtained. Allergic sensitization was assessed by a skin prick test to mite allergens. Spearman's rank-order correlation was used to assess the correlation between the intake frequencies of 16 food types. Dietary patterns were identified using principal component analysis. Four corresponding dietary scores were derived to examine the association of identified dietary patterns with allergic sensitization and AD exacerbations through a multivariable logistic regression that controlled for age, gender, parental eczema, BMI, and lifestyle factors. Results The correlation is the strongest between the intake of butter and margarine (R = 0.65). We identified four dietary patterns, "high-calorie foods", "plant-based foods", "meat and rice", and "probiotics, milk and eggs", and these accounted for 47.4% of the variance in the dietary habits among the subjects. Among these patterns, moderate-to-high intake of "plant-based foods" conferred a negative association for chronic (Adjusted odds ratio (AOR): 0.706; 95% confidence interval (CI): 0.589-0.847; p < 0.001) and moderate-to-severe AD (AOR: 0.756; 95% CI: 0.638-0.897; p < 0.01). "Meat and rice" and "probiotics, milk and eggs" were not significantly associated with AD exacerbation. While frequent adherence to "high-calorie foods" increased the associated risks for ever AD and moderate-to-severe AD, having a higher adherence to "plant-based foods" diminished the overall associated risks. Conclusions Frequent adherence to "plant-based foods" was associated with reduced risks for AD exacerbation in young Chinese adults from Singapore/Malaysia. This provides the initial evidence to support the association between dietary factors and AD. Further research is needed to better understand the pathomechanisms underlying diet and AD exacerbations.